Da’wah in Muhammadiyah Education: Muhammadiyah Renewal for Islamic Education in West Sumatra - Sarwan Sarwan; Fatimah Azzahra; Sabaruddin Sabaruddin (Institut Agama Islam Negeri Bengkulu, 2022)
Education has been a significant focus for the Muhammadiyah organization in Indonesia. Unfortunately, this sector has yet to be studied as a massive da'wah movement. This study discusses how da'wah has been transformed into education. The mission of inviting people to God's way has been practised gently. This article discusses the history of Muhammadiyah education renewal, explaining the history of Muhammadiyah education and revealing the renewal of Muhammadiyah education. West Sumatra has been designated as a case study explained using a literature approach. This research relies on secondary data through searching Muhammadiyah books, articles and websites. The results of this study indicate: firstly, the history of Muhammadiyah education renewal was triggered by the condition of Muslims in Indonesia and the influence of reformers from the Middle East and the Archipelago. Secondly, the history of Muhammadiyah education in West Sumatra begins with the establishment of executive branches. The third, Muhammadiyah is reforming Islamic education in West Sumatra by changing traditional education to a modern system. Third, the renewal of Muhammadiyah education is oriented towards da'wah, in which the marginalized, orphan and converts become inseparable.